Examining the Role of Networking, Organizational Culture, and Information System Quality in the Implementation of Strategic Management Accounting Methods Using Structural Equation Modeling - Pezashkizadeh, Reza; Mahmoudi, Ali; Kaab Omeir, Ahmad; Avazzadeh Fath, Fariborz (Management Strategies and Engineering Sciences, 2023)
This research examines the factors influencing the implementation of strategic management accounting methods. Based on library research and statistical analyses, this study investigates the role of three variables—networking, organizational culture, and information system quality—in the implementation of these methods. The study is applied in terms of its outcome and is classified as descriptive-survey research in terms of its goal. The statistical population consists of manufacturing and industrial companies listed on the Tehran Stock Exchange in 2022, totaling 287 companies, with 166 questionnaires used for the analysis. Hypothesis testing was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM), along with t-statistics, significance levels, and path coefficients. The research utilized Excel 2016, SmartPLS 3, and SPSS 26 software. The results indicate that networking, innovation-based culture, results-based culture, and information system quality significantly influence the implementation of strategic management accounting methods. Furthermore, information system quality significantly affects the role of networking and the implementation of these methods. While innovation-based culture has a significant indirect effect on the implementation of strategic management accounting methods through the mediating role of networking, this indirect effect was not confirmed for results-based culture. Based on the findings, it can be stated that the implementation of strategic management accounting methods is more likely in organizations with effective and extensive communication networks, high-quality information systems, and an innovation- and results-driven culture. Additionally, the use of effective communication networks, coupled with a quality information system, and supported by an innovation-based culture, facilitates the implementation of these methods. In results-based cultures, managers will continue to study and gather the necessary information to achieve strategic organizational goals, even in the absence of effective communication networks.